(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The preamble ofIndian Constitution is a mirror to the constitutional spirit. It implicates theconcepts of secularism socialism, Justice, equality and liberty ant theultimate aim is fraternity which the country has to achieve with theenforcement of the constitutional provisions. We remain under the foreign rulefor a long span of time. Just after independence it was very crucial to makethe high level effort to establish a just and fundamental freedom and move onthe path of development. So, some legal and constitutional guidelines wererequired for the same. This need and spirit was imbibed in the constitution andthis very spirit of equality, Justice, liberty, secularism, socialism,fraternity, separation of powers, theory of check and balances, theory ofguided powers, positive morality, Non-violation of the basic structure is called constitutionalism.